Diseño eléctrico de un sistema de recarga rápida (electrolinera) para baterías de vehículos eléctricos. - Quizhpe Conde, Luis Alexander (2018)
The present thesis work consists to accomplish an electrical design of a fast-recharged station for electric cars that could be installed in Loja city. The rules considered for this electric station design are locals, nationals, and internationals. As well as the usage of the bibliography referent to electric vehicles and types of charges. This thesis arose from the need for a quick recharging point in our city because most of the electric vehicles are for public transport use and have to travel many kilometers discharging their batteries in a matter of a few hours, so when they have to be re-charged at their house, work time is lost. Then the theme of an electric station or service station with energy dispensers for the batteries of electric vehicles was taken. At the moment of the design of the electric station, 4 energy dispensers were proposed and, of course, comfortable areas were taken in consideration for the owners of the vehicles so their waiting time is more pleasant. This thesis is supported by previous research work, catalogs for electric vehicles, regulations or standards related to electric mobility. The electric design of the electric station comprises the MV connection, which supplies 13.8 kV from EERSSA. The connection arrives at the transformation center that feeds the 300 kVA pad-mounted mesh type transformer for the fast chargers. Since the 300 kVA transformer is mesh type you can derive an MV line to the 15 KVA transformer that will serve us for services such as lighting and outlets. The dispatch area of the electric station is designed for the installation of 4 chargers or power dispensers.